2011
DOI: 10.1186/1472-6955-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing nurses' compliance with Standard Precautions in order to avoid occupational exposure to microorganisms: A focus group study

Abstract: BackgroundNurses may acquire an infection during the provision of nursing care because of occupational exposure to microorganisms. Relevant literature reports that, compliance with Standard Precautions (a set of guidelines that can protect health care professionals from being exposed to microorganisms) is low among nurses. Additionally, high rates of exposure to microorganisms among nurses via several modes (needlesticks, hand contamination with blood, exposure to air-transmitted microorganisms) occur. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
178
1
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(211 citation statements)
references
References 57 publications
18
178
1
14
Order By: Relevance
“…It was found that the result of current study is far from what can be acknowledged as standers practice of UPs where, the high percent of studied groups reported unavailability of suitable number of personal protective equipment such as gown, masks, gloves, aprons and goggles. This finding was congruent with the study conducted by Efstathiou et al (2011) who stated that, the most important factor to non-adherence of HCPs with protective barrier was the lack of protective equipment available. Haile et al (2017) added that, frequent unavailability of PPE could decrease the impulse of active staff and could be a reason for nonadherence.…”
Section: Part Iii: Resourcessupporting
confidence: 82%
“…It was found that the result of current study is far from what can be acknowledged as standers practice of UPs where, the high percent of studied groups reported unavailability of suitable number of personal protective equipment such as gown, masks, gloves, aprons and goggles. This finding was congruent with the study conducted by Efstathiou et al (2011) who stated that, the most important factor to non-adherence of HCPs with protective barrier was the lack of protective equipment available. Haile et al (2017) added that, frequent unavailability of PPE could decrease the impulse of active staff and could be a reason for nonadherence.…”
Section: Part Iii: Resourcessupporting
confidence: 82%
“…The identified factors include: lack of knowledge, lack of personal protective equipment (PPE), high workload, low risk perception and low perception of institutional safety environment. 9,21 Our study demonstrated that 59.2% of HCWs were complaining of deficiencies of hand washing facilities on the ward including absence of hand wash stations which was also confirmed by observational checklists, 65.3% complaining of making patient-care very technical, while 51% complaining of irritation effect of hand hygiene product. Similarly Duerink et al 9 reported a striking shortage of hand washing facilities.…”
mentioning
confidence: 68%
“…A study done by Efstathiou et al has shown inadequate compliance concerning hand hygiene guidelines with precautions among nurses in order to avoid exposure to microorganisms use of gloves when exposure to body fluids was anticipated. 1 Another study has also shown that perceived barriers to compliance with UPs clearly influence HCW's ability and willingness to comply with them in practice. 9 Inability to use PPE during emergencies, overwork and busy schedules have also been shown in similar settings.…”
Section: Resultsmentioning
confidence: 99%
“…Health care professionals and particularly nurses are often exposed to microorganisms, many of which can cause serious or even lethal infections. 1 Although the potential for HBV transmission in the workplace setting is greater than for HIV, the mode of transmission for these two viruses are the same. According to a WHO study, the annual estimated proportions of health care workers exposed to blood borne pathogens globally were 2.6% for HCV, 5.9% for HBV and 0.5% for HIV worldwide.…”
Section: Introductionmentioning
confidence: 99%